RAINWATER ARCHITECTURE Reimagining Kungstorget for Gothenburg’s 400 year jubilee - Larsson, Filip (My University, 2023)
The purpose of this master thesis is to investigate, relating to the Gothenburg 400 year jubilee effort ”Rain Gothenburg”, what it means - in practice - to be the best city when it rains. Western countries - Sweden included - today handle water in a wasteful, non-reflective manner as if it was an endless resource. Even though Gothenburg isn’t facing a fresh water drought in the near future thanks to Göta Älv, the city - with the intent of being the best city when it rains - needs to become an exemplary model for how rain and cloudburst elegantly could be turned from a problem to a resource for the urban development. Moreover, the population of denser urban areas are increasingly seeking refuge in rural environments for health and wellbeing. Has the city failed its inhabitants to provide the right preconditions for leading healthy, fullworthy lives? Studies show that presence of green and especially blue spaces generate less subscriptions of antidepressants. Could, then, dense urban environments become healthier environments, if blue spaces are tightly interwoven with the everyday urban spaces? This thesis therefore explores how rain in Gothenburg can be integrated in a central urban setting - utilized through new additions on Kungstorget - in order to generate awareness of the potential of rainwater as a resource, and to create intimate spaces and an increased proximity to blue spaces in central urban spaces, for enhanced experiences, healthier and more meaningful environments. The project aims to re-establish the teeming life on Kungstorget, replacing parking lots with rainwater experiences and spaces for trade and interaction. The design is informed partly by historical, cultural and contemporary analyzes, and partly by how the architecture should interact with the rainwater chain. This method could generate a teeming urban hub that demonstrates how Gothenburg is turning rain from an inconvenience to an asset, in the attempt of being the best city when it rains.
Keywords: Rain interventions, Phenomenology, Blue space, Atmosphere, Construction